2014
DOI: 10.1063/1.4860775
|View full text |Cite
|
Sign up to set email alerts
|

Thermal coupon testing of Load-Bearing Multilayer Insulation

Abstract: Abstract. Advanced liquid hydrogen storage concepts being considered for long duration space travel incorporate refrigeration systems and cryocoolers to lower the heat load. Using a refrigeration loop to intercept the energy flowing through MLI to a liquid hydrogen tank at a temperature between the environment and the liquid hydrogen can lower the heat load on the propellant system by as much as 50%. However, the refrigeration loop requires structural integration into the MLI. Use of a more traditional concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…14 At KSC, testing was performed between 77 K and various warm boundary temperatures between 293 K and 325 K on Cryostat-100. 15 Testing showed that there was no additional penalty due to the seaming methods used in LB-MLI and that the thermal penalties due to perforations were also small enough to ignore. …”
Section: A Coupon Testingmentioning
confidence: 97%
“…14 At KSC, testing was performed between 77 K and various warm boundary temperatures between 293 K and 325 K on Cryostat-100. 15 Testing showed that there was no additional penalty due to the seaming methods used in LB-MLI and that the thermal penalties due to perforations were also small enough to ignore. …”
Section: A Coupon Testingmentioning
confidence: 97%
“…Generally, MLI systems are used in high vacuum environments, which may be a vacuum vessel or space such as planet's orbits and surfaces [7]. This is because MLI is the ideal insulation for the radiation dominated heat transfer environments such as space orbits and other high vacuum applications [20]. Furthermore, MLI systems can also be designed for soft vacuum purposes in industrial products as well as in commercial building apparatus [21].…”
Section: Re-emitted Radiationmentioning
confidence: 99%
“…Generally, MLI systems are used in high vacuum environments, which may be a vacuum vessel or space such as the Earth's orbit or the lunar surface [7]. This is because MLI is the ideal insulation for the radiation dominated heat transfer environments such as spacecraft in the low Earth orbit and the other high vacuum functions [20]. Furthermore, MLI systems can also be designed for soft vacuum purposes in industrial products as well as in commercial building apparatus [21].…”
Section: Introductionmentioning
confidence: 99%